2016
DOI: 10.1126/scisignal.aaf3204
|View full text |Cite
|
Sign up to set email alerts
|

H 2 S production by reactive oxygen species in the carotid body triggers hypertension in a rodent model of sleep apnea

Abstract: Sleep apnea is a prevalent respiratory disease in which episodic cessation of breathing causes intermittent hypoxia. Patients with sleep apnea and rodents exposed to intermittent hypoxia exhibit hypertension. The carotid body senses changes in blood O2 concentrations and an enhanced carotid body chemosensory reflex contributes to hypertension in sleep apnea patients. Using a rodent model of intermittent hypoxia that simulates blood O2-saturation profiles of patients with sleep apnea, increased generation of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 46 publications
1
49
0
1
Order By: Relevance
“…However, research in recent years has convincingly demonstrated the role of H 2 S as an endogenous gasotransmitter with importance on par with that of nitric oxide (NO) and carbon monoxide (CO) . H 2 S has been shown to have anti‐inflammation, antitumor, ion channel regulation, cardiovascular protection, and antioxidation effects . Along with these physiological roles, H 2 S is emerging as a potential therapeutic agent much the same way as NO and CO …”
Section: Introductionmentioning
confidence: 99%
“…However, research in recent years has convincingly demonstrated the role of H 2 S as an endogenous gasotransmitter with importance on par with that of nitric oxide (NO) and carbon monoxide (CO) . H 2 S has been shown to have anti‐inflammation, antitumor, ion channel regulation, cardiovascular protection, and antioxidation effects . Along with these physiological roles, H 2 S is emerging as a potential therapeutic agent much the same way as NO and CO …”
Section: Introductionmentioning
confidence: 99%
“…The role of CO-H 2 S signaling in IH-evoked carotid body activation was examined (Yuan et al , 2016). This study showed that ROS generated during IH inhibits HO-2-dependent CO generation and this effect requires Cys 265 in the heme regulatory motif of HO-2.…”
Section: Introductionmentioning
confidence: 99%
“…The decreased CO in turn increases H 2 S production by activating CSE. Inhibiting CSE-derived H 2 S synthesis either by genetic knock down of CSE or by pharmacological blockade prevents the chemo- reflex activation and hypertension in IH treated rats (Yuan et al , 2016). These findings demonstrate that ROS is epistatic to H 2 S in driving chemo-reflex-dependent hypertension by IH (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11–13] Perturbations in CO and H 2 S interplay are associated with sleep apnea and other (patho)physiological conditions. [12,14] Currently, there is limited knowledge of the interplay of CO and H 2 S and no molecular tools are available to study their interactions. This arena differs from that of NO/H 2 S interactions wherein a significant body of research is available.…”
mentioning
confidence: 99%